Frequency control reserve with multiple micro grid participation for power system frequency stability - Mohamad Syamin Bin Zainal Abidin; Norhafiz Bin Salim; Aimie Nazmin Bin Azmi; Nor Aira Binti Zambri; Takao Tsuji (Institute of Advanced Engineering and Science, 2019)
The introduction of this micro grids into the conventional distribution network system forces a new challenge to the system operation. The failure factor of the power system performance essentially due to the limitation of electrical power generation in which could not meet the load demand. In order to maintain the frequency stability of the system, the power sources must be matched instantaneously among all generators and constantly supply to the load demand. A deviation of system frequency from the set-point value will affect the entire stability of power system network. This paper investigates the impact of utilizing multiple micro grids in supporting and facilitating on grid’s frequency. A method called Frequency Control Reserve (FCR) is introduced, with intention to share the excessive power from all available micro grids. These power will be controlled effectively before being injected into the main grid to stabilize the power frequency. Simulation using MATLAB Simulink have been used to simulate the result and shows great potential to be integrated with distributed generation i.e. solar photovoltaic (PV) for Malaysia power system vicinity.